Bioactive conformation of stromelysin inhibitors determined by transferred nuclear Overhauser effects. - Gonnella, N C (1995)
The transferred nuclear Overhauser effect has been used to determine the biologically active conformations of two stromelysin inhibitors. Both inhibitors used in this study were hydroxamic acids generated via chemical synthesis. These structures, representing the conformation of each inhibitor bound to stromelysin, superimposed with excellent agreement. The study also provided information on the shape and orientation of the S2' and S1' pockets of the enzyme relative to thermolysin. Comparisons were made between stromelysin and thermolysin inhibitors to critically examine thermolysin as a template for stromelysin-inhibitor design. The enzyme-bound conformations of these stromelysin inhibitors were determined for use as a template in conformationally restricted drug design.